Rentabilidad de la producción de panela artesanal en el sitio agua fría del cantón Junín - Baquero Díaz, Julio César (2012)
This thesis entitled Profitability of traditional production of handmade panela in Agua Fría in Junín canton was done through a field and descriptive research, which contributed to get dates about a productive activity such as the panela production. The visiting of the producers was useful to obtain details of the processes and production costs as well as to determine the profitability and create a base line to help producers know more about this industrial activity. The profitability of this production was determined by the rate of economics profitability with the data taken from producers through surveys and economics information. It was also noticed that producers do not know the legal procedures related to their properties, businesses, and health permissions. The lack of knowledge of administrative issues, marketing plans avoids them to improve and develop a better production. The presentation of the results was held in a meeting with the producers to show the findings and recommendations to show them profitability rates obtained from their panela production and to encourage them to attend training courses to improve their facilities, processes, distribution channels and marketing to carry their business in a more efficient way.